TYPE 2 DIABETES MELLITUS AnEvidence-BasedApproach to Practical Management - Mark N. Feinglos, md, cm , M. Angelyn Bethel, md (2008)

(untitled)
TYPE 2 DIABETES MELLITUS AnEvidence-BasedApproach to Practical Management